2021
DOI: 10.1109/access.2021.3082847
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Non-Idealities in the Generation of Reconfigurable Sinc-Shaped Optical Nyquist Pulses

Abstract: Optical sinc-shaped Nyquist pulses are widely used in microwave photonics, optical signal processing, and optical telecommunications due to their numerous advantages, like rectangular shape in the frequency domain, the orthogonality and the consequential possibility to use these pulses to transmit data with the maximum possible symbol rate. Ideal sinc pulses with the rectangular spectrum are just a mathematical construct. However, high-quality sinc pulse sequences offer the same advantages and can be generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The effect of non-idealities on the sinc-shaped Nyquist pulse generation has been studied in detail for different rollof-factor, ripple and sideband suppression ratios [34], [35]. Compared to an ideal flat comb, a 2 dB ripple in a 3-line comb only increases the root mean square error of the pulses by 3%.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of non-idealities on the sinc-shaped Nyquist pulse generation has been studied in detail for different rollof-factor, ripple and sideband suppression ratios [34], [35]. Compared to an ideal flat comb, a 2 dB ripple in a 3-line comb only increases the root mean square error of the pulses by 3%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the second derivatives y ′′ i can be obtained as the solution of the following linear system of equations b = Ey (6) where y = [y ′′ 1j , y ′′ 2j , . .…”
Section: B Using Cubic Polynomial Functions For the Geometrical Const...mentioning
confidence: 99%
“…The most popular design satisfying the above mentioned requirements is the socalled raised-cosine (RC) pulse [3], which has been widely employed in numerous practical digital communications systems, e.g. see [5], [6], [7], [8], [9], [10], and [11] and references therein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Previously, the effect of non-idealities for the frequency comb generation by Mach-Zehnder modulators at the transmitter side has been studied in detail for the research project Metrology for THz Communications (Meteracom). [25][26][27][28] For the receiver side, it has been shown that orthogonal sampling can effectively enhance the ENOB. 23,24 In this study, we investigate the impact of the case that the carrier is higher than the sidebands (positive ripple) on the performance of orthogonal sampling.…”
Section: Introductionmentioning
confidence: 99%